THE EFFECTIVENESS OF LOCAL DEMOCRATIC SYSTEMS IN REALIZING GOOD GOVERNANCE - Hilman Sutanto (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
This research aims to examine the effectiveness of the local democracy system in promoting the realization of good governance principles at the regional government level. The study was conducted using a literature review approach by analyzing various scientific sources such as journals, academic books, and relevant policy reports. The focus of the discussion includes three main aspects: public participation in policy formulation, transparency and accountability of local government, and the challenges and solutions in the implementation of local democracy. The study results indicate that local democracy has strong potential in promoting good governance if implemented in a participatory, open, and responsible manner. However, challenges such as corruption, money politics, elite dominance, and weak oversight institutions still pose serious obstacles. Therefore, structural reforms, regulatory strengthening, bureaucratic capacity building, and participatory innovation are needed to ensure that local democracy can function effectively as an instrument of good governance.